2017
DOI: 10.1016/j.cropro.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Drought-tolerant Desmodium species effectively suppress parasitic striga weed and improve cereal grain yields in western Kenya

Abstract: AbstractsThe parasitic weed Striga hermonthica Benth. (Orobanchaceae), commonly known as striga, is an increasingly important constraint to cereal production in sub-Saharan Africa (SSA), often resulting in total yield losses in maize (Zea mays L.) and substantial losses in sorghum (Sorghum bicolor (L.) Moench). This is further aggravated by soil degradation and drought conditions that are gradually becoming widespread in SSA. Forage legumes in the genus Desmodium (Fabaceae), mainly D. uncinatum and D. intortum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Furthermore, to expand the push-pull technology to drought-prone areas, climate-adapted push-pull technology using drought tolerant Desmodium spp. and Napier grass (or other grasses) as the intercrop and border crop, respectively, has been developed [141,142,[144][145][146][147]. This improved technology is currently practised by more than 54,000 farmers in East Africa [142] and a higher percentage of women perceived the improved technology as very effective compared to men [146].…”
Section: Intercropping and Mixed Croppingmentioning
confidence: 99%
“…Furthermore, to expand the push-pull technology to drought-prone areas, climate-adapted push-pull technology using drought tolerant Desmodium spp. and Napier grass (or other grasses) as the intercrop and border crop, respectively, has been developed [141,142,[144][145][146][147]. This improved technology is currently practised by more than 54,000 farmers in East Africa [142] and a higher percentage of women perceived the improved technology as very effective compared to men [146].…”
Section: Intercropping and Mixed Croppingmentioning
confidence: 99%
“…(generally referred to as Striga) infestations: one 7-year study in Kenya determined that several edible legume species, including crotalaria and groundnut (Arachis hypogaea L.), reduced Striga hermonthica emergence by up to 35% (Midega et al 2014). A more recent study by Midega et al (2017) indicated that drought-tolerant Desmodium [Desmodium uncinatum (Jacq.) DC.…”
Section: Intercroppingmentioning
confidence: 99%
“…This is set to improve further by the introduction of even more drought‐tolerant and insect‐resistant Brachiaria spp. cultivars and newly identified intercrops such as D. incanum …”
Section: Crop Protection From Secondary Plant Metabolism By Companionmentioning
confidence: 99%
“…6 Related signalling in the rhizosphere shows promise for crop protection 7 wileyonlinelibrary.com/journal/ps Figure 1. The push-pull for the control of stemborer moth larval damage to cereals on small holder farms in sub-Saharan Africa is explained in this annotated cartoon, and in the text, 5,9 for the further control of the parasitic weed Striga hermonthica 8,10 and more recently for the fall armyworm. 11,12 This push-pull intervention against the pests and the agro-ecological advantages of plant nutrition and other factors 13 gives three fold cereal yields with no seasonal inputs of fertilizer or pesticide even under climate change stress.…”
Section: Crop Protection From Secondary Plant Metabolism By Companionmentioning
confidence: 99%